2015
DOI: 10.1016/j.jfma.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the root and root canal systems of mandibular first premolars in northern Taiwanese patients using cone-beam computed tomography

Abstract: Approximately 82% of mandibular first premolars in northern Taiwanese patients have one root with either one or two canals. There are significant differences in the number of roots and canals and symmetry of the root canal system of bilateral mandibular first premolars between male and female northern Taiwanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
8
18
0
1
Order By: Relevance
“…While the high and significant values of Spearman’s rank correlation coefficient in both the groups validate the reliability of the method used to measure the repair cementum thickness in this study, other factors may have played a role in causing this variability including (i) variations in root anatomy and surface morphology which can be seen between contralateral teeth also [19, 20], leading to different stress distribution in PDL. This can cause different levels and patterns of resorption on different areas of the root [21]; (ii) errors in the initial cut after decalcification, which divides the specimen into two for embedding into paraffin.…”
Section: Discussionsupporting
confidence: 58%
“…While the high and significant values of Spearman’s rank correlation coefficient in both the groups validate the reliability of the method used to measure the repair cementum thickness in this study, other factors may have played a role in causing this variability including (i) variations in root anatomy and surface morphology which can be seen between contralateral teeth also [19, 20], leading to different stress distribution in PDL. This can cause different levels and patterns of resorption on different areas of the root [21]; (ii) errors in the initial cut after decalcification, which divides the specimen into two for embedding into paraffin.…”
Section: Discussionsupporting
confidence: 58%
“…Descriptive statistics were expressed as mean values and standard deviations, frequencies, or percentages as appropriate for each measurement calculated at person and tooth levels. The chi-square test was used for examining differences with categoric variables such as age (age <50 vs age $50 years) (30), sex (male vs female), side (left vs right), and DLR group (non-DLR, Uni-DLR, and Bil-DLR) (30). To evaluate the independent effect on the canal configurations of PMLIs, a multivariable logistic regression analysis was used and was simultaneously adjusted for other confounding variables, such as sex, age, and side.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these studies are a valuable data source on the relationship between age and root canal anatomy, they have limitations, including small samples sizes (Huang et al 2015, Naseri et al 2016, limited groups of teeth (Neaverth et al 1987, Nosrat et al 2015 or a restricted methodology such as, identification of extra root canals during root canal treatment or using periapical radiographs (Thomas et al 1993). These methods might not be able to represent the three-dimensional nature of the root canal anatomy clearly.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of previous CBCT studies reveals that only a single group of teeth (Huang et al 2015) or a single root (Lee et al 2011) was reported on, or the study just addressed the prevalence of a specific extra canal in a specific root (Kim et al 2012, Guo et al 2014, or a specific root canal configuration such as the C-shaped mandibular molar (Kim et al 2016, Martins et al 2016. Even when combining all the available data, it is not possible to gain an overall understanding of the changes within the root canal system configuration over time because many groups of teeth have not been studied using CBCT technology.…”
Section: Introductionmentioning
confidence: 99%